H.O. Penn : 'managing by values' brought the company back, but now will it guide its growth? - Barton-Sweeney, Alexandra; Podolny, Joel M. (Joel Marc); Baron, James N.; Elias, Jaan ([London] : SAGE, 2016)
In 1991, Tom Cleveland, CEO and owner of the Caterpillar dealership, H.O. Penn Machinery Company, found himself contemplating the sale of his poorly performing business, which had been in his family for nearly three decades. After he was unable to reach an agreement with a particular buyer, however, Cleveland re-committed himself to H.O. Penn, determined to turn around its fortunes. This study explains how Cleveland set about introducing a management system called 'Managing by Values', which would ultimately infuse explicitly stated values and goals into every facet of the company's operations.
Originally Published in: Barton-Sweeney, A., Podolny, J., Baron, J. N., & Elias, J. (2007). H.O. Penn: `Managing By Values' Brought the Company Back, But Now Will it Guide its Growth?. 07-013. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Corporations -- Growth -- Case studies; Organizational change -- Management -- Case studies; Corporate culture -- Case studies